Quality-Adjusted Life-Years Lost Due to Physical Inactivity in the United States Osteoarthritis Population - Losina, Elena (Arthritis Care Res (Hoboken), 2020)
OBJECTIVE: Half of the 14 million persons in the US with knee osteoarthritis (OA) are not physically active, despite evidence that physical activity (PA) is associated with improved health. We estimated both the quality-adjusted life-year (QALY) losses in the US knee OA population due to physical inactivity and the health benefits associated with higher PA levels. METHODS: We used data from the Osteoarthritis Initiative and CDC to estimate the proportions of the US knee OA population aged 45+ that are inactive, insufficiently active, and active and their likelihoods of shifting PA level. We used the Osteoarthritis Policy (OAPol) Model, a computer simulation of knee OA, to determine QALYs lost due to inactivity and to measure potential benefits (comorbidities averted and QALYs saved) of increased PA. RESULTS: Among 13.7 million persons living with knee OA, 7.5 million total QALYs, or 0.55 QALYs/person, were lost due to inactivity or insufficient PA relative to activity over their remaining lifetimes. Black Hispanic women experienced the highest losses, 0.76 QALYs/person. Females of all races/ethnicities had ~20% higher loss burdens than males. According to our model, if 20% of the inactive population were instead active, 95,920, 222,413, and 214,725 potential cases of cancer, cardiovascular disease, and diabetes would be averted, and 871,541 potential QALYs would be saved. CONCLUSION: Physical inactivity leads to substantial QALY losses in the US knee OA population. Increasing activity level in even a fraction of this population may have considerable collateral health benefits, potentially averting cases of cancer, cardiovascular disease, and diabetes.